2022
DOI: 10.37201/req/s03.13.2022
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in donation and transplant

Abstract: SARS-CoV-2 infection has had a major impact on donation and transplantation. Since the cessation of activity two years ago, the international medical community has rapidly generated evidence capable of sustaining and increasing this neccesary activity. This paper analyses the epidemiology and burden of COVID-19 in donation and transplantation, the pathogenesis of the infection and its relationship with graft-mediated transmission, the impact of vaccination on donation and transplantation, the evolution of dona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…In the literature, few studies have been published on the evaluation of the short-term outcomes in patients who received various transplant from SARS-CoV-2 positive donors. Although the data is very limited, they reported that the recipients receiving products from these donors does not adversely affect engraftment or survival ( 19 , 20 ). Despite these findings, the drafting of official guidelines of the national transplant center will be necessary for planning future cryopreserved ovarian tissue transplant in patient SARS-CoV-2 positive at the time of ovarian tissue retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, few studies have been published on the evaluation of the short-term outcomes in patients who received various transplant from SARS-CoV-2 positive donors. Although the data is very limited, they reported that the recipients receiving products from these donors does not adversely affect engraftment or survival ( 19 , 20 ). Despite these findings, the drafting of official guidelines of the national transplant center will be necessary for planning future cryopreserved ovarian tissue transplant in patient SARS-CoV-2 positive at the time of ovarian tissue retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…(kidney, liver, and heart) being transplantation a safe practice, with a low risk of transmission, regardless of the presence of symptoms at the time of procurement [8].…”
Section: Introductionmentioning
confidence: 99%
“…The impact on organ transplantation also varied with respect to organ type with preferential deferral of kidney transplant candidates who were stable on renal replacement therapy and/or had lower immunologic barriers to transplantation [ 4 ]. However, the majority of reports noted a decline in SOT in all organ types, with living donor programs generally suspended or curtailed in many sites [ 5 - 7 ], recent evidence has also shown that there is low risk for a transplant recipient to get infected from an already infected donor, especially in non-pulmonary organs (kidney, liver, and heart) being transplantation a safe practice, with a low risk of transmission, regardless of the presence of symptoms at the time of procurement [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation